Mechanical Properties of Laminated Veneer Lumber (LVL) Fabricated from Three Malaysian Hardwood Species - Norshariza Mohamad Bhkari; Lum Wei Chen; Muhammad Shaiful Nordin; Nazatul Syuhada Zainal; Za'ba, Nurul Izzatul Lydia; Zakiah Ahmad (International Journal of Integrated Engineering, 2023)
The application of laminated veneer lumber (LVL) has long been limited to non-structural elements in Malaysia. The LVL is commonly fabricated with veneer from low to medium density (290 to 630 kg/m3) softwood or temperate hardwood. The data on the properties of LVL made from medium to high density (567 to 687 kg/m3) tropical hardwood species is very limited. Therefore, this study investigated the mechanical and bonding properties of LVL fabricated from Malaysian hardwood species namely Kasai (Pometia spp.), Mengkulang (Heritiera spp.) and Kedondong (Canarium spp.). Different variables were studied: i) wood species; ii) loading surface (flatwise or edgewise), iii) grain direction (parallel and perpendicular), iv) treatment condition. The bending and compression test was carried out in accordance with EN 408:2012, while the block shear test was conducted based on EN14374:2004 and EN 314-1:2004. The results shows that the grain direction has the most significant effect (P â‰¤ 0.01) on the bending, compressive and bonding properties of the samples tested. The treatment conditions for block shear test also displayed significant effect on its shear strength. The samples loaded parallelly displayed bending values 320-450% higher than the samples loaded at perpendicularly. The compressive strength and compressive modulus are 323-365% and 523-2530% respectively when loaded parallelly. LVL performed better mechanically when loaded parallelly and when subjected to less extreme treatment conditions.